THE RELATIONSHIP BETWEEN LIFESTYLE AND WEIGHT STATUS AMONG SENIOR HIGH SCHOOL STUDENTS IN INDONESIA: A CASE STUDY IN LAMPIHONG - Khoiriyati, Khoiriyati; Basit, Mohammad; Onieqie Ayu Dhea M; Latifah, Latifah (STIKES Suaka Insan, 2025)
The increasing prevalence of Non-Communicable Diseases (NCDs) constitutes a global health challenge driven by unhealthy lifestyle risk factors. This phenomenon is now increasingly widespread among adolescents, potentially affecting their weight status. This study aimed to analyze the relationship between lifestyle and weight status among adolescents at SMAN 1 Lampihong. This quantitative study employed a correlational design with a cross-sectional approach. A sample of 68 students was selected via purposive sampling. Data were analyzed using univariate analysis for frequency distribution and bivariate analysis using the Spearman rank correlation test. The results indicated that a majority of respondents (58.8%) had an unhealthy lifestyle, and 41.2% had an abnormal weight status based on Body Mass Index (BMI). However, the correlation test revealed no statistically significant relationship between the two variables (p = 0.219; ? = 0.05). It was concluded that within this study population, no significant relationship exists between lifestyle and adolescent weight status.